XY0206 targets FLT3-dependent resistance states in acute myeloid leukemia - Long Shen; Yang Yang; Chenghua Xu; Bo Jiang; Xiaoxiao Duan; Xianfeng Shao; Simeng Li; Siyi Liu; Chao Huang; Lin Song; Mingyuan Sun; Jinting Fan; et al. (Journal of Clinical Investigation, 2026)
Activating mutations in FMS-like tyrosine kinase 3 (FLT3) drive aggressive acute myeloid leukemia (AML) and confer poor prognosis. Although FLT3 inhibitors have improved outcomes, their efficacy is frequently limited by microenvironment-mediated signaling and treatment-emergent resistance. XY0206 is a structurally optimized derivative of sunitinib, an inhibitor approved for multiple solid tumors. Biochemical, multi-omics, and functional analyses showed that XY0206 directly engages FLT3 and suppresses downstream STAT5, AKT, and ERK signaling, resulting in apoptosis in FLT3 -ITD AML cells. Across models of FLT3-dependent resistance, XY0206 retained antileukemic activity, including in FLT3 -ITD cells harboring the F691L gatekeeper mutation, a recurrent alteration conferring resistance to approved FLT3 inhibitors. In primary AML blasts and xenograft models, XY0206 exhibited enhanced antileukemic activity with favorable tolerability relative to gilteritinib. In a phase I/II trial (NCT04471064) of XY0206 monotherapy in patients with relapsed or refractory (R/R) AML, XY0206 achieved a composite complete remission rate (CRc) of 45.7% overall, with a notable 60.0% CRc rate among patients with FLT3 -ITD mutations. Three of eight patients with prior FLT3 inhibitor-exposed R/R AML also achieved CRc. Together, these findings support further clinical evaluation of XY0206 as a FLT3-directed therapeutic in AML, particularly in disease settings with reduced sensitivity to existing FLT3 inhibitors.